Research in Distance Education: A Status Report - Saba, Farhad (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2000)
Since the 1950s and expansion of social science research, distance education has been studied in comparison to face-to-face or classroom instruction. Although researchers continue to conduct comparative studies, their usefulness in revealing more information has diminished over the years; invariably, they have returned a “no significant difference” result between various forms of instruction. In recent years, researchers have moved beyond atheoretical, experimental comparative studies and have introduced new methods, such as discourse analysis, and in-depth interview of learners. These new methods overcome many methodological and theoretical limitations of the physical science view of distance education. These studies have further revealed the complexity of distance education, indicating the many variables involved in the concept. Starting with the core issue of instructional interaction and grounded on the theory of transactional distance, a new strand of research using methods related to systems dynamics, hierarchy and complexity theories, promises a more comprehensive understanding.